The U(1)A Anomaly and QCD Phenomenology - Graham Shore (Lecture Notes in Physics, 2007)
The role of the U(1)A anomaly in QCD phenomenology is reviewed, focus- ing on the relation between quark dynamics and gluon topology. Topics covered include a generalisation of the Witten-Veneziano formula for the mass of the η′, the determina- tion of pseudoscalar meson decay constants, radiative pseudoscalar decays and the U(1)A Goldberger-Treiman relation. Sum rules are derived for the proton and photon structure functions g1p and g1γ measured in polarised deep-inelastic scattering. The first moment sum rule for g1p (the ‘proton spin’ problem) is confronted with new data from COMPASS and HERMES on the deuteron structure function and shown to be quantitatively explained in terms of topological charge screening. Proposals for experiments on semi-inclusive DIS and polarised two-photon physics at future ep and high-luminosity e+e− colliders are discussed.